Plasma treatment of polymethyl methacrylate to improve surface hydrophilicity and antifouling performance. Issue 2 (30th November 2020) - Sui, Siyuan; Li, Lin; Shen, Jie; Ni, Guohua; Xie, Hongbin; Lin, Qifu; Zhao, Yanjun; Guo, Jingwei; Duan, Wenxue
Abstract: Surface modification of polymethyl methacrylate (PMMA) by O2 /CF4 plasma is investigated to improve hydrophilicity and antifouling performance of PMMA. The PMMA surface before and after treatment is characterized by atomic force microscopy, contact angle measurement, and X‐ray photoelectron spectroscopy. Antifouling properties are evaluated by protein adsorption and bacterial adhesion experiments using Staphylococcus aureus in vitro. Higher O2 content in the mixture gas promotes hydrophilicity of the plasma‐treated PMMA, while a hydrophobic surface forms at higher CF4 content. Modifying PMMA improves antifouling performance regardless of the O2 /CF4 volume ratio, and this improvement increases with rising CF4 content in O2 /CF4 plasma working gas. Functional groups CO and CF are detected in O2 /CF4 plasma‐treated PMMA surface and the ratio of CO to CF can be controlled by the O2 /CF4 volume ratio in the plasma working gas. Abstract :